Ammonia exposure impairs lateral-line hair cells and mechanotransduction in zebrafish embryos. (October 2020) - Lin, Li-Yih; Zheng, Jie-An; Huang, Shun-Chih; Hung, Giun-Yi; Horng, Jiun-Lin
Abstract: Ammonia (including NH3 and NH4 + ) is a major pollutant of freshwater environments. However, the toxic effects of ammonia on the early stages of fish are not fully understood, and little is known about the effects on the sensory system. In this study, we hypothesized that ammonia exposure can cause adverse effects on embryonic development and impair the lateral line system of fish. Zebrafish embryos were exposed to high-ammonia water (10, 15, 20, 25, and 30 mM NH4 Cl; pH 7.0) for 96 h (0–96 h post-fertilization). The body length, heart rate, and otic vesicle size had significantly decreased with ≥15 mM NH4 Cl, while the number and function of lateral-line hair cells had decreased with ≥10 mM NH4 Cl. The mechanoelectrical transduction (MET) channel-mediated Ca 2+ influx was measured with a scanning ion-selective microelectrode technique to reveal the function of hair cells. We found that NH4 + (≥5 mM NH4 Cl) entered hair cells and suppressed the Ca 2+ influx of hair cells. Neomycin and La 3+ (MET channel blockers) suppressed NH4 + influx, suggesting that NH4 + enters hair cells via MET channels in hair bundles. In conclusion, this study showed that ammonia exposure (≥10 mM NH4 Cl) can cause adverse effects in zebrafish embryos, and lateral-line hair cells are sensitive to ammonia exposure. Graphical abstract: Image 1 Highlights: The body length, heart rate, and size of the otic vesicle of zebrafish embryos decreased after ammonia exposure. The number and function of lateral-line hair cells decreased after ammonia exposure. Ambient NH4 + entered hair cells and suppressed Ca 2+ influx of hair cells. Lateral-line hair cells were sensitive to ammonia exposure.